(untitled) (Journal of Plant Disease Sciences, 2019)
The present study was concerned with the formulations of suitable culture media for growth of nitrogen fixing, phosphate soulbilizing and potash mobilizing bacteria in a consortium. Among the different culture media, MS III media having Glucose (10 g/L), Mannitol (10 g/L), Ammonium sulphate (0.5 g/L) and Yeast extract (6 g/L) recorded maximum growth and cfu count of Rhizobium, PSB and KMB. These three beneficial microorganisms found compatible with each other when grown on MS III culture media. Seed inoculation of green gram with consortia of MPKV Rhizobium, PSB and KMB +75% RDF significantly increase the number of branches (4.75), Plant height (60.50 cm), number of nodules/plant (41.50) and chlorophyll content (0.8368 mg/g) and found at par with 100% RDF.The maximum number of pods/plant (8.00) yield/plant (16.75g) and dry matter/plant (24.25g) were recorded in treatment of 100% RDF but found at par with seed inoculation with consortia of MPKV Rhizobium, PSB and KMB +75% RDF which recorded number of pods/plant, yield/plant and dry matter/plant 7.25, 15.50 g and 23.50 g, respectively. The significantly highest available ‘N’ 164 kg/ha, ‘P’ 28 kg/ha and ‘K’ 800 kg/ha were recorded in seed inoculation with consortia of MPKVRhizobium, PSB & KMB consortia + 75% RDF followed by 100% RDF.Seed inoculation with consortia of MPKV Rhizobium, PSB and KMB significantly increased the growth and yield of greengram as compared to uninoculated control.